Major depression-related immunological changes and combination antiretroviral therapy in HIV-seropositive patients - Alciati, Alessandra; Gallo, Luciana; Monforte, Antonella D'Arminio; Brambilla, Francesca; Mellado, Carmen (Human psychopharmacology, 2007)
Background In physically healthy subjects, major depression has been associated with several changes in immune function. In HIV‐infected subjects too, lymphocyte subsets changes related to psychological conditions have been described. Objective The aim of this study was to investigate the effect of major depression on immunological parameters in HIV‐infected subjects and to examine the influence of different potency antiretroviral therapies on depression‐related immunological changes. Method Thirty‐six HIV‐infected patients with major depression treated with different potency antiretroviral therapies (none, double, triple) were compared with 77 matched non‐depressed HIV controls with regard to demographic, clinical and immunological parameters. Results The presence of depression was a significant predictor of natural killer (NK) cell number and percentage decline. Antiretroviral therapy and depression‐antiretroviral therapy interaction do not significantly influence depression‐related NK cell changes. Conclusions The study confirms the role of depression in influencing the immune response in HIV‐seropositive subjects and suggests that antiretroviral therapies may not be able to hamper the depression‐related NK cell changes even using the most potent regimens such as Highly Active Antiretroviral Therapy (HAART). Copyright © 2007 John Wiley & Sons, Ltd.